FIRE-SAFE CIGARETTES - THERIEN,EJ (Tufts Archival Research Center, 2007)
Marginalia; News release from Canada Safety Council announcing its recommendation to Federal Health Minister that fire safe cigarette issue be given high priority. Includes letter from Emile-J. Therien, President of Canada Safety Council, to David Dingwall, Minister of Health. Provides statistics about cigarette-related fire and associated injury while discussing political context in Canada and related issues in the United States.